Understanding Islamic Economics as an Islamic Moral Economy - Ahmadi, Abdul Zahoor; Afifah, Ade Muthia; Qarar, Walid; Atiqi, Hasibullah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study explores Islamic economics as a moral economy, emphasizing its ethical foundations derived from Shariah principles. Islamic economics contrasts with conventional systems by prioritizing justice, social welfare, and the equitable distribution of wealth over profit maximization. Key concepts such as Zakat (almsgiving), the prohibition of Riba (interest), and ethical financial practices aim to address global economic challenges like inequality, poverty, and financial instability. Through a qualitative case study, this research critically analyzes how Islamic economic principles can be applied to contemporary economic issues. The study highlights both the potential of Islamic economics to offer sustainable and equitable solutions and the challenges of integrating these principles into global financial systems, particularly due to diverse interpretations and structural limitations. The findings contribute to a deeper understanding of how Islamic economics can inspire ethical reforms in global economic practices.